2013
DOI: 10.1002/j.0022-0337.2013.77.1.tb05451.x
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Left‐Handed Dental Students and Interns in Saudi Arabia

Abstract: The purpose of this study was to survey left-handed (LH) dental students and interns concerning whether they face any problems in their dental education or in their practice of dentistry. The questionnaires were distributed in four dental colleges in different regions in Saudi Arabia. The questionnaire was comprised of sixteen questions to assess the following issues: demographic information, dificulties in dental school or dental practice due to left-handedness, preferred hand in performing different dental p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
3
15
1
Order By: Relevance
“…When looking at the distribution of handedness, the percentage of participants stating left-handedness in the present study was about 10.6 percent. This is comparable to the percentage found in another study among dentists [ 21 , 22 ]. However, this percentage may vary widely, between around 2 and 30 percent [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When looking at the distribution of handedness, the percentage of participants stating left-handedness in the present study was about 10.6 percent. This is comparable to the percentage found in another study among dentists [ 21 , 22 ]. However, this percentage may vary widely, between around 2 and 30 percent [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the mental application of the sequence might have been easier for the right-handed rather than for the left-handed participants, resulting in more time being required for implant insertion for the left-handed participants. In a recent examination, it was reported that left-handed dental students had problems when being instructed by right-handed tutors [ 21 ]. This, however, was not assessed in our examination.…”
Section: Discussionmentioning
confidence: 99%
“…Dentistry is a demanding profession that requires fine motor skills, spatial perception and high level of accuracy . It also requires concentration, coordination and the ability to work on a small scale . Delivery of successful dental treatment depends upon multiple factors that include position and anatomy of the tooth, selection of proper instrument, correct angulation of the instrument and manual skills.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of either the right or the left hand to operate is not a choice and changing one's handedness is not easy . In most dental schools, the techniques used as well as the chairs and equipment available are mainly designed to suit right‐handed operators …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation